Character Based Islamic Education Among The Millennial Generation - Uyun, Nadrotul; Ismawati, Siti; Taslim, Muhammad; Inayah, Bidayatul; Farhanudin, A. (The Magister of Islamic Education IAIN Pontianak, 2025)
The aim of this research is to gain an understanding of the role of Islamic education in shaping the character of the millennial generation at MTs Al Khairiyah. In the current era of globalization, the millennial generation faces many complex problems, such as technological advances and the fast flow of information. One method that can help the younger generation face this problem is character-based Islamic education. This research identifies the character values taught to Islamic Religious Education (PAI) teachers, the problems faced by teachers, and the teaching approaches used. This research uses qualitative methods by conducting in-depth interviews with these teachers. The research results show that character-based Islamic education at MTs Al Khairiyah plays an important role in forming students' character, although there are several difficulties in implementing it.